Queen of the Andes: the ecology and conservation of Puya raimondii - Fortier, Riley P. (Frontiers in Conservation Science, 2024)
Puya raimondii is the world’s largest bromeliad and a prime example of a “charismatic megaflora”. Indeed, its grand stature and remarkable once-in-a-lifetime flowering event have earned it the name “Queen of the Andes”. Like many Puya species, it is one of the only large-statured plants in high Andean puna ecosystems and an important structural and ecological component throughout its native range, providing food and shelter to a variety of animals. However, its future is threatened by anthropogenic stressors such as climate change and land use. In this article, I provide a review of its life history, ecology, and the most important threats to the plant, including climate change and land use. Despite its importance, status as endangered, and the urgency of its threats, little is being done to forecast its future and protect its scattered populations. I finally call for its conservation through in- and ex-situ initiatives and argue that future intervention will be necessary to ensure its survival.